(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to reveal the effect of the knowledge harvest strategy on the achievement of the students of the Institute of Fine Arts in the subject of the foundations of design addition to the research problem, its importance and the limits of the research. It included first-year students studying the subject of design foundations and defining the terms mentioned in the title of the research. The second chapter included the theoretical framework and harvest strategy Knowledge, achievement, and the foundations of design material, in addition to the previous studies and their discussion. In the third chapter, the research procedures, as the researcher adopted the experimental method, the community, the sample, the research tool, honesty, stability and application, in addition to the statistical methods. The fourth chapter concluded that there is a significant impact in the knowledge harvest strategy in the achievement of the students of the Institute of Fine Arts in basics. Design, conclusions, recommendations and suggestions, then a list of sources and appendices